Актуализация национальной мифологемы в условиях иностранного топоса («Лесная песня» Леси Украинки) - Левчук, Юлія Олександрівна; Levchuk, Yuliia O. (v. Javakhishvili Tbilisi State University ; Shota Rustaveli Institute of Georgian Literature, 2013)
В статье исследуется проблема творчества автора в условиях эмиграции, в частности пребывание Леси Украинки в Грузии, где она создала драму-феерию «Лесная песня». Обращено внимание на функции мифологемы в исследуемом тексте как универсальной схемы мира. Важными в аспекте этого исследования являются мнемонические особенности писательници, тоесть её способность к извлечению из памяти давно усвоенной информации. Кроме того, статья касается вопроса о культурной (коллективной) памяти, механизмы которой запускаются неосознанно. Теория коллективной памяти очень тесно связанна с концепцией «коллективного бессознательного» К. Г. Юнга, что позволяет исследователю говорить о «взаимодействии культур» (по Ю. Лотману), в данном случае, грузинской и украинской.

In the article the author examines the problem of creativity in terms of emigration, particularly Lesia Ukrainka’s stay in Georgia, where she has created a drama-extravaganza «Forest Song». Attention is given to the function mythological scheme in the study text as a universal scheme in the world. An important aspect in this study are the mnemonic features of writer, her ability to extract from memory long ago assimilated the information. In addition, the article refers to the issue of cultural (collective) memory, mechanisms that triggered unconsciously. The theory of collective memory is very closely connected with the concept of «collective unconscious» of C. G. Jung, which allows the researcher to talk about «the interaction of cultures» (in Y. Lotman), in this case, the Georgian and Ukrainian.
A ctualization of National Mythologeme in the Conditions of Foreign Topose (Lesia Ukrainka’s «The Forest S ong»)
Keywords: мифологема; mythological scheme; драма-феерия; drama extravaganza; мнемонические способности; mnemonic abilities; коллективная память; collective memory